2009
DOI: 10.1002/maco.200805118
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical response of amorphous and devitrified Al‐Ni‐La‐X (X = Ag, Cu) alloys

Abstract: The electrochemical response of melt-spun Al-Ni-La alloys with partial substitution of Ni after different stages of devitrification was studied. The base alloy was found to have the best corrosion resistance. It was observed that primary crystallization caused minimal deterioration in the corrosion resistance of the base alloy as compared to its amorphous state. The substitute alloys had different corrosion resistance dependent on the substituting element with the Ag containing alloy having the least resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Apart from the aforementioned coatings, many researchers have studied corrosion behavior of Al-based melt-spun amorphous ribbons to understand the effect of various element substitution and partial or complete devitrification on corrosion resistance. [36][37][38][39][40][41][42][43][44][45][46][47] Retention of corrosion resistance with partial devitrification or formation of nanocrystalline phases in the amorphous matrix is still debatable, although it is an established fact that corrosion resistance deteriorates with complete devitrification. Figure 34 shows the E true versus log i anodic plots for Al 87 Ni 8.7 Y 4.3 and Al 90 Fe 5 Gd 5 glassy ribbons in nitrogen-purged 0.6 M NaCl solution indicating retention of corrosion resistance in the amorphous condition during the corrosion test.…”
Section: Corrosion Behavior Of Al-based Amorphous Ribbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the aforementioned coatings, many researchers have studied corrosion behavior of Al-based melt-spun amorphous ribbons to understand the effect of various element substitution and partial or complete devitrification on corrosion resistance. [36][37][38][39][40][41][42][43][44][45][46][47] Retention of corrosion resistance with partial devitrification or formation of nanocrystalline phases in the amorphous matrix is still debatable, although it is an established fact that corrosion resistance deteriorates with complete devitrification. Figure 34 shows the E true versus log i anodic plots for Al 87 Ni 8.7 Y 4.3 and Al 90 Fe 5 Gd 5 glassy ribbons in nitrogen-purged 0.6 M NaCl solution indicating retention of corrosion resistance in the amorphous condition during the corrosion test.…”
Section: Corrosion Behavior Of Al-based Amorphous Ribbonsmentioning
confidence: 99%
“…However, some researchers have assigned the covering of nearly homogeneous Al-rich oxides and the interface between amorphous/nanocrystalline α-Al phase, which may promote diffusion of passive elements to enhance the formation of protective passive film. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] With further devitrification, the microgalvanic coupling effect between different crystalline phases becomes active. In addition, grain boundary area of various crystalline phases increases, which decreases the corrosion resistance.…”
Section: Corrosion Behavior Of Al-based Amorphous Ribbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum based bulk metallic glasses (Al-BMG) have attracted a lot of attention due to their superior mechanical properties, low density and corrosion resistance [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical studies on Al-BMG have shown superior corrosion resistance as compared to pure Al [5][6][7][8]18]. Xueqing et al have studied the corrosion resistance of the melt-spun amorphous Al 88 Ni 6 La 6 and Al 86 Ni 6 La 6 Cu 2 in 0.01 M alkaline NaCl [6].…”
Section: Introductionmentioning
confidence: 99%